Mix design considerations and performance characteristics of foamed bitumen mixtures (FBMs) - Kuna, Kranthi (2015)
The sustainability issues in pavement materials and design form a strong incentive for the present work. Using recycled materials in pavements is a sustainable practice that is gaining adoption, particularly for flexible (bituminous) pavements. One approach is to incorporate large quantities of Reclaimed Asphalt Pavement (RAP) into base and sub-base applications for pavement construction. Numerous studies have reported that RAP can be reused as an aggregate in Hot Mix Asphalt (HMA) as well as in cold mix asphalt, granular base, sub-base, and subgrade courses. Cold recycling technology, like hot mix technology, has also become popular in various countries for rehabilitation of damaged bituminous pavements. RAP stabilized with bitumen emulsion and foamed bitumen has been used as a base layer. The present study focuses on Foamed Bitumen treated Mixes (FBMs). Most of the agencies which use FBMs have their own mix design procedures which are the result of numerous efforts over decades. In spite of all these efforts, Foamed Bitumen application in cold recycling in the United Kingdom suffers from the lack of a standardised mix design procedure. To overcome this, the present research objective was to develop a mix design procedure by identifying critical mix design parameters. The mix design parameters that were optimised were Foamed Bitumen content, mixing water content (MWC), and compaction effort. Special attention was given to the simplest yet crucial mix design consideration of FBMs; curing. The thesis also attempted to simulate what should be expected in terms of the performance of flexible pavements containing FBMs as road base.